Tutor-student interaction: how advice is requested, offered, and responded to in an online consultation. - Tebele, Tebele Sharon (University of the Witwatersrand, Johannesburg, 2024)
In many university courses, tutors and students engage in online consultations for tutors providing students with academic support. Part of a tutor’s responsibility in such an interaction is to give the student academic advice. Previous studies have been done on how students accept or resist advice in in-person interactions, but the online tutor-student consultation has not been investigated. I focus on advice giving and explore how advice is requested, offered, and responded to in an online tutor-student consultation using an ethnomethodologically informed conversation analytic approach. To do this, I examine a single 27-minute audio recording of an online tutor-student consultation. The session was voluntarily recorded on the online meeting platform and both the tutor and student consented to sharing it with me. Through a tutor-led interrogative sequence, the tutor builds a common ground and establishes an epistemic equilibrium where both tutor and student are knowledgeable about the student’s experiences. Thereafter, the student may issue a troubles telling that shifts the epistemic gradient so that the tutor is in a more knowledgeable position and able to offer advice regarding the trouble. I also investigate an instance where the student does not issue a troubleshooting, and the tutor does not offer advice. My findings align with the recommendations by a previous study that advice-giving can be evaluative: as the tutor only advised after the student had shared their thoughts and knowledge about the topic to determine if there was a need for advice. The findings contribute to the literature on advice sequences in institutional settings by reinforcing prior findings and demonstrating how the tutor used a series of techniques to build common ground and epistemic equilibrium and how the student used a troubles telling to shift the epistemic gradient so the tutor could move into a more knowledgeable position necessary for giving advice. While there has been limited research conducted on advice-giving in face-to-face T-S interactions to my knowledge, there has been no investigation of how advice is accomplished in online T-S consultations to highlight the originality of the current study.
A research report Submitted in fulfillment of the requirements for a Master’s Degree in Psychology, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Conversation analysis; tutor-student interaction; online consultation; epistemics; advice-giving; SDG-4: Quality education